No refuge in the whole wide world - Eishan Jan, Mohammad Naqib (2018)
Hassan Al-Kontar, a Syrian asylum seeker who is stranded in the transit lounge of Kuala Lumpur International Airport since March 7, is a victim of the armed conflict in his country. The conflict in Syria began in 2011 when peaceful protests were met with violent crackdowns by security forces. The brutal conflict has continued until today.